Novel application of an imageless robotic system in simultaneous unicompartmental knee arthroplasty and anterior cruciate ligament reconstruction - Joshua Yeuk Shun Tran; Rex Wang-Fung Mak; Kevin Ki-Wai Ho; Jonathan Patrick Ng; Cham Kit Wong; Gloria Yan-Ting Lam; Tsz Lung Choi; Michael Tim-Yun Ong; Patrick Shu-Hang Yung (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
This technical note explores the novel use of an imageless robotic surgical system for simultaneous unicompartmental knee arthroplasty (UKA) and anterior cruciate ligament reconstruction (ACLR). Knee osteoarthritis (OA) and anterior cruciate ligament (ACL) insufficiency are common conditions that traditionally require separate management. The integration of robotic assistance offers enhanced precision in surgical procedures, addressing both medial compartment OA and ACL insufficiency in a single operation.We present a case involving a 47-year-old patient with medial compartment osteoarthritis and complete ACL rupture. The patient underwent a simultaneous robotic-assisted UKA and ACLR using the CORI Surgical System (Smith&Nephew, London, UK). This approach enables accurate tibial tunnel placement and precise soft tissue balancing. The robotic system facilitates real-time gap assessment and balancing, reducing the risk of over- or under-constraint during ACL graft tensioning.The procedure was performed with a standard medial parapatellar approach. Key steps included hamstring autograft harvesting, femoral and tibial tunnel creation, and robotic-assisted implant positioning. Post-operative rehabilitation allowed full weight-bearing by the third week.This case represents the first reported instance of using an imageless robotic system for simultaneous UKA and ACLR, highlighting its potential to standardize and improve results in complex knee surgeries.This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.